Semiempirical model for analysis of inhomogeneous optically thick laser-induced plasmas - D'angelo, Cristian Adrián (2009)
Abstract In this paper, a more realistic approach of a non-uniform optically thick plasma in local thermodynamic equilibrium was applied to describe self-reversal of Co I 340.51 nm emission line recorded from a laser-induced plasma generated on a Co Cr Mo metallic alloy. This line was selected because it is one of the most absorbed of the major elements in air at atmospheric pressure. The model describes the behavior of the plasma after the breakdown, and it was semiempirical thus, some information was taken from the experiment. A cylinder-symmetrical plasma column with a parabolic temperature distribution having a maximum at the center and decreasing toward the edges was considered. The input parameters were the plasma length, the temperature in the plasma core, and the Co total density, which were estimated from measurements and previous work. Moreover, the distribution of electron density depended on the temperature, and the ionization degree was taken into account through Saha equation. Then, plasma parameters were adjusted in such a way calculations reproduced the experimentally measured line profiles. The effect of varying laser power on plasma homogeneity and its evolution in time were investigated. Moreover, preliminary results of spatial distribution of plasma parameters were obtained that confirmed the practical application of the model on plasma diagnostics.